Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Pendekatan Economic Value Added (EVA) dan Market Value Added (MVA) pada Perusahaan Farmasi yang Go Public di Bursa Efek Indonesia Tahun 2008-2011 - Eskasari, Weny Mey; dro, Harlen (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Better economic growth gives opportunity for business people to increase their profits. At the other side, it is also increase tight rivalry between businesses. Good performance management is needed in order to achieve the company's goals and to maximalize investor’s prosperity. This study uses descriptive quantitative method, which aims to determine the company's financial performance using analysis tools Economic Value Added (EVA) and Market Value Added (MVA) in pharmaceutical companies, namely PT. Darya Varia Laboratories Tbk, PT. Kalbe Farma Tbk, PT. Merck Tbk, PT. Pyridam Farma Tbk, and PT. Tempo Scan Pacific Tbk. The data used in this study is a secondary data obtained from Pojok BEI Faculty of Economics and Business Universitas Brawijaya Malang. The result shows that during the four (4) years of the study, five pharmaceutical companies are producing positive EVA value. It means that management has succeeded in creating added value for its investors because it met the investors’s expectations to earn returns over the issuance of capital. While the MVA value shows diverse results. Positive result of MVA indicates that the management has been able to increase the wealth of its investors, while a negative value indicates that the MVA management has demolished the wealth of its investors. Keywords : Financial Performance, Economic Value Added (EVA), Market Value Added (MVA)